Concepts and characteristics of the 'COST Reference Microplasma Jet'. (20th January 2016) - Golda, J; Held, J; Redeker, B; Konkowski, M; Beijer, P; Sobota, A; Kroesen, G; Braithwaite, N St J; Reuter, S; Turner, M M; Gans, T; O'Connell, D; et al.
Abstract: Biomedical applications of non-equilibrium atmospheric pressure plasmas have attracted intense interest in the past few years. Many plasma sources of diverse design have been proposed for these applications, but the relationship between source characteristics and application performance is not well-understood, and indeed many sources are poorly characterized. This circumstance is an impediment to progress in application development. A reference source with well-understood and highly reproducible characteristics may be an important tool in this context. Researchers around the world should be able to compare the characteristics of their own sources and also their results with this device. In this paper, we describe such a reference source, developed from the simple and robust micro-scaled atmospheric pressure plasma jet ( μ -APPJ) concept. This development occurred under the auspices of COST Action MP1101 'Biomedical Applications of Atmospheric Pressure Plasmas'. Gas contamination and power measurement are shown to be major causes of irreproducible results in earlier source designs. These problems are resolved in the reference source by refinement of the mechanical and electrical design and by specifying an operating protocol. These measures are shown to be absolutely necessary for reproducible operation. They include the integration of current and voltage probes into the jet. The usual combination of matching unit and power supply is replaced by an integrated LC power coupling circuit and a 5 W single frequency generator. The design specification and operating protocol for the reference source are being made freely available.